2005
DOI: 10.1016/j.cub.2005.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin Promotes Cell Motility by Enhancing Lamellipodial Persistence

Abstract: Cortactin enhances lamellipodial persistence, at least in part through regulation of Arp2/3 complex. The presence of cortactin also enhances the rate of new adhesion formation in lamellipodia. In vivo, these functions may be important during directed cell motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
294
2
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(332 citation statements)
references
References 40 publications
34
294
2
2
Order By: Relevance
“…Moreover, cortactin potentiates bone metastasis of breast cancer cells in nude mice (Li et al, 2001). Lastly, recent findings demonstrate that fibrosarcoma cells deficient in cortactin have impaired cell migration and invasion, underscoring the role of cortactin in cell motility (Bryce et al, 2005). Histone deacetylases (HDACs) are enzymes that catalyse the removal of the acetyl moieties from the e-amino group of the lysine residues in histone and nonhistone proteins (Cress and Seto, 2000;Grozinger and Schreiber, 2002;Blander and Guarente, 2004;Gregoretti et al, 2004;Glozak et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cortactin potentiates bone metastasis of breast cancer cells in nude mice (Li et al, 2001). Lastly, recent findings demonstrate that fibrosarcoma cells deficient in cortactin have impaired cell migration and invasion, underscoring the role of cortactin in cell motility (Bryce et al, 2005). Histone deacetylases (HDACs) are enzymes that catalyse the removal of the acetyl moieties from the e-amino group of the lysine residues in histone and nonhistone proteins (Cress and Seto, 2000;Grozinger and Schreiber, 2002;Blander and Guarente, 2004;Gregoretti et al, 2004;Glozak et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One such gene encodes a protein similar to cortactin-binding protein 2. The orthologous cortactin-binding protein 90 associates with cortactin, a multidomain scaffolding protein involved in actin polymerization (38). In the rat, the known expression of cortactinbinding protein 90 is restricted to the brain (39).…”
Section: Resultsmentioning
confidence: 99%
“…Cortactin-S298A Enhances Polarized Cell Migration-Because we have already shown that the activity status of PKD affects Panc89 as well as breast cancer cell motility (1-3) and cortactin has been published to affect cell migration (16) we were prompted to test whether cortactin or its respective S298A mutation would alter migration of Panc89 cells toward a chemotactic serum gradient in Transwell migration assays. In line with Ref.…”
Section: Pkd-mediated Phosphorylation Of Cortactin At Sermentioning
confidence: 99%
“…Cortactin was further shown to co-localize with proteins of the Arp2/3 complex at sites of actin polymerization within lamellipodia (12). It synergistically accelerates Arp complex-mediated actin polymerization (15) and has been shown to promote cell migration by enhancing lamellipodia persistence (16). We have thus investigated a role of PKD as an upstream regulator of cortactin and its function in actin organization as well as cell migration.…”
mentioning
confidence: 99%